2020
DOI: 10.3390/socsci9040044
|View full text |Cite
|
Sign up to set email alerts
|

Professional Values Challenged by Case Management—Theorizing Practice in Child Protection with Reflexive Practitioners

Abstract: In this article, we theorize and reflect based on former research into professional practice and discretion as well as use some results from working together with practitioners in child protection services to explore the phenomenon of non-performing. Regulation lies at the heart of the contemporary child protection discourse. On the one hand we have seen a trend towards systematization of assessment content and procedures, on the other hand it is assumed that rational management approaches can secure consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…deadlines) and make informed decisions (BLD 2013(BLD , 2019Lipsky 2010), even the most dedicated, child-centred caseworker can feel the need to prioritise performance demands over the children's right to express their views on their own terms. These findings illustrate that caseworkers may need to make their work look good on paper instead of relying on values derived from social work theory (Marthinsen et al 2020). As previous researchers point out (Ferguson 2016;Munro 2002), caseworkers are in a dual relationship because they are expected to reach informed conclusions and provide appropriate services in accordance with the CPS system's procedures and performance measures and, at the same time, to build trustful relationships with parents and children.…”
Section: Discussionmentioning
confidence: 79%
“…deadlines) and make informed decisions (BLD 2013(BLD , 2019Lipsky 2010), even the most dedicated, child-centred caseworker can feel the need to prioritise performance demands over the children's right to express their views on their own terms. These findings illustrate that caseworkers may need to make their work look good on paper instead of relying on values derived from social work theory (Marthinsen et al 2020). As previous researchers point out (Ferguson 2016;Munro 2002), caseworkers are in a dual relationship because they are expected to reach informed conclusions and provide appropriate services in accordance with the CPS system's procedures and performance measures and, at the same time, to build trustful relationships with parents and children.…”
Section: Discussionmentioning
confidence: 79%
“…We should bear in mind that this sample reported having a high caseload, and this hinders their capacity to find the time and space for reflecting on the work developed. Other studies have also reported these high caseloads (e.g., Leigh and Miller 2004;Marthinsen et al 2020). Moreover, as we highlight in the results (Section 3.2), supervision is not included as a mandatory activity for most social workers in Mallorca (Spain), and this may contribute to not finding reflection spaces.…”
Section: Discussionmentioning
confidence: 87%
“…Engelbertink et al (2022) argue that students should be supported in this aspect of their studies as they develop their professional identity. Gunetilleke et al (2011) and Marthinsen et al(2020) argue that the increasing predominance of liberal economic thought, which influences developmental discourse and practice, is a key factor in these tensions. Gunetilleke et al (2011) further argue that perceived tensions may be addressed through either resolving these or by individuals choosing to work in areas which align more closely with their own values.…”
Section: Tensions Between Personal Professional and Institutional Valuesmentioning
confidence: 99%
“…Such tensions are heightened for community development practitioners, as the profession is continually seeking to balance whose values should prevail, foregrounding those of the communities where they work, especially as these are in a "constant process of becoming" (Banks, 2019, p.196). Similarly, qualified Social Workers can find that the bureaucracy where they work operates a different set of values to those of the profession (Marthinsen et al, 2020). The tensions inherent in this situation means that all possible values cannot be realised simultaneously.…”
Section: Tensions Between Personal Professional and Institutional Valuesmentioning
confidence: 99%
See 1 more Smart Citation